Liver Blood Flow as a Major Determinant of the Clearance of Recombinant Human Tissue-Type Plasminogen Activator - de Boer, A; Kluft, C; Kroon, J M; Kasper, F J; Schoemaker, H C; Pruis, J; Breimer, D D; Soons, P A; Emeis, Jef J; Cohen, Adam F (Thrombosis and Haemostasis, 1992)
The influence of changes in liver blood flow on the clearance of rt-PA was studied both in healthy subjects and in a perfused rat liver model. Liver blood flow in healthy subjects was documented indirectly by the clearance of indocyanine green (ICG). Exercise reduced liver blood flow on average by 57% with a 95% confidence interval (95% Cl) ranging from 51% to 62% (n = 5) and increased plasma levels of rt-PA activity (after an i. v. infusion of 18 mg of rt-PA over 120 min) by 119% (95% Cl, 58% - 203%) and rt-PA antigen by 91% (95% Cl, 30% - 140%). In the perfused rat liver model it was shown that halving or doubling of the physiological flow rate of a perfusate, containing rt-PA caused a proportional change in the clearance of rt-PA, while the extraction of rt-PA by the liver remained similar. In conclusion, liver blood flow is a major determinant of the clearance of rt-PA. This may have important implications for dosage of rt-PA in patients with myocardial infarction.